How common is add-on use and how do patients decide whether to use them? A national survey of IVF patients. Issue 7 (4th May 2021) - Lensen, S; Hammarberg, K; Polyakov, A; Wilkinson, J; Whyte, S; Peate, M; Hickey, M
Abstract: STUDY QUESTION: What is the prevalence and pattern of IVF add-on use in Australia? SUMMARY ANSWER: Among women having IVF in the last 3 years, 82% had used one or more IVF add-on, most commonly acupuncture, preimplantation genetic testing for aneuploidy and Chinese herbal medicine. WHAT IS KNOWN ALREADY: IVF add-ons are procedures, techniques or medicines which may be considered nonessential to IVF, but usually used in attempts to improve the probability of conception and live birth. The use of IVF add-ons is believed to be widespread; however, there is little information about the prevalence and patterns of use in different settings. STUDY DESIGN, SIZE, DURATION: An online survey was distributed via social media to women in Australia who had undergone IVF since 2017. Women were excluded if they were gestational surrogates, used a surrogate, or underwent ovarian stimulation for oocyte donation or elective oocyte cryopreservation only. The survey was open from 21 June to 14 July 2020. PARTICIPANTS/MATERIALS, SETTING, METHODS: Survey questions included demographics, IVF and medical history, and use of IVF add-ons including details of the type of add-on, costs and information sources used. Participants were also asked about the relative importance of evidence regarding safety and effectiveness, factors considered in decision-making and decision regret. MAIN RESULTS AND THE ROLE OF CHANCE: A total of 1590 eligible responses were analysed. Overall, 82% of women had used one or more add-ons and these usually incurred an additional cost (72%). Around half (54%) had learned about add-ons from their fertility specialist, and most reported that the decision to use add-ons was equally shared with the specialist. Women placed a high level of importance on scientific evidence for safety and efficacy, and half (49%) assumed that add-ons were known to be safe. Most women experienced some regret at the decision to use IVF add-ons (66%), and this was more severe among women whose IVF was unsuccessful (83%) and who believed that the specialist had a larger contribution to the decision to use add-ons (75%). LIMITATIONS, REASONS FOR CAUTION: This retrospective survey relied on patient recall. Some aspects were particularly prone to bias such as contributions to decision-making. This approach to capturing IVF add-on use may yield different results to data collected directly from IVF clinics or from fertility specialists. WIDER IMPLICATIONS OF THE FINDINGS: There is a very high prevalence of IVF add-on use in Australia which may be generalisable to other settings with similar models of IVF provision. Although women placed high importance on scientific evidence to support add-ons, most add-ons do not have robust evidence of safety and effectiveness. This suggests that IVF patients are not adequately informed about the risks and benefits of IVF add-ons, or are not aware of the paucity of evidence to support their use. STUDY FUNDING/COMPETING INTEREST(S): This research was supported by a McKenzie Postdoctoral Fellowship Grant (University of Melbourne), a Department of Obstetrics and Gynaecology Innovation Grant (University of Melbourne) and an NHMRC Investigator Grant (APP1195189). A.P. declares that he provides fertility services at Melbourne IVF (part of Virtus Health). J.W. reports grants from Wellcome Trust, during the conduct of the study, and that publishing benefits his career. The remaining authors report no conflict of interest. TRIAL REGISTRATION NUMBER: N/A